2008
DOI: 10.1542/peds.2007-1220
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid-Induced Lung Injury in Newborn Infants: A Bronchoalveolar Lavage Fluid Study

Abstract: Bile acids are detectable in the bronchoalveolar lavage fluid of newborns from intrahepatic cholestasis of pregnancy affected by respiratory distress syndrome. Elevated serum bile acid levels in these infants allow us to hypothesize that bile acid reaches the lung after an uptake from the circulation. These findings strongly support a role for bile acid in causing bile acid pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 22 publications
0
54
0
3
Order By: Relevance
“…This suggests that, in addition to Foxm1b, FXR may regulate expression of other genes during acute lung repair. We should also note that FXRϪ/Ϫ mice have increased bile acid levels that may be related to certain lung injury (30). Therefore, whether FXR in other organs besides lung also involve in the LPS-induced lung injury needs more investigation.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that, in addition to Foxm1b, FXR may regulate expression of other genes during acute lung repair. We should also note that FXRϪ/Ϫ mice have increased bile acid levels that may be related to certain lung injury (30). Therefore, whether FXR in other organs besides lung also involve in the LPS-induced lung injury needs more investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have showed that high concentration of bile acid gathered in alveolus cleaning solution in ICP neonates [22], but the incidence of ICP in neonatus had no direct correlation with bile acid concentration in amniotic fluid, while it had close relationship with high bile acid level in fetal blood [2, 23]. Our results demonstrate that (1) bile acid concentration of fetal rats serum in dose group was significantly higher than that of the experimental group and blank control group, and there is positive correlation between TBA of pregnant rat serum and that of fetal rat serum; (2) the still birth rate in dose groups was significantly higher than that of the experimental group and blank control group.…”
Section: Discussionmentioning
confidence: 99%
“…There is understandably a paucity of studies done on humans but experimental studies conducted on rats [10], rabbits [11] and pigs [12], have demonstrated that bile acids cause inflammation and cytotoxic effects on histologic examinations. Similarly, broncho-alveolar lavage studies have found a positive correlation between increased bile acid levels and inflammatory markers in blood, increased neutrophilia [13], inflammation in alveoli and ventilator associated pneumonias [9]. Likewise visceral inflammation and injury of lungs, larynxes were found to be related to Bile Juice reflux independently of acid reflux in gastroesophageal reflux diseases [6].…”
Section: Discussionmentioning
confidence: 95%